The dark side - Steel, Danielle (London : Pan Books, 2019)
The Dark Side is a powerful and unsettling novel of loss, motherhood and the innocence of childhood from the world$1 (Bs favourite storyteller, Danielle Steel. Zoe Morgan was just ten years old when her life changed forever. Her sister, Rose, died of a rare illness, her parents turned into people she didn$1 (Bt know, and Zoe$1 (Bs lonely childhood drove her to excel in her studies. As a graduate of Yale, Zoe takes a leave of absence from medical school to work in a shelter for abused children in New York, where she meets well-known child advocacy attorney, Austin Roberts. Austin is bowled over by her beauty, brains and talent. He is her first love and the man she marries. Austin and Zoe have a perfect life and, after the birth of their longed-for daughter Jaime, Zoe knows that the aching void she had lived through for twenty-four years is finally complete. But it is only then that the true impact of Rose$1 (Bs death all those years ago affects their lives in a way that nobody could ever have imagined.s
Keywords: Fiction